A model for companies to overcome US–China conflict on international trade - Sousa, M.; Sousa, M.; Cruz, R. V. (Management and Economics Research Journal, 2019)
This article aims to study international trade specificity and the main activities of Chinese companies in US markets. It addresses the strategic tools of companies and their application in a global and very competitive market, framed by public policies and governments’ strategies. It explores the principles of the internal and external environment of the countries. The main research question is: what are the dimensions of a model to potentiate the US–China Companies? The principal methodology used in this research was a literature review, and the analysis was based on the papers that research the theme US and China trade relations. The findings reflect that international trade is conditioned by the government politics, and there are several other obstacles that a US or Chinese company need to overcome: (a) economic forces; (b) technological forces; (c) political–legal forces; (d) sociocultural forces; and (e) physical forces.